The science of story characters: a neuroimaging perspective on antagonists in narrative engagement - Obando Yar, Alejandra; Moret-Tatay, Carmen; Esteve Rodrigo, José Vicente (Frontiers in Human Neuroscience, 2025)
IntroductionUnderstanding how humans perceive and engage with fictional characters—particularly antagonists—offers valuable insights into narrative comprehension and moral cognition. Antagonists, as morally complex figures, challenge readers’ ethical frameworks and stimulate affective and cognitive responses. This review aims to synthesize current research on the neural mechanisms involved in the perception and evaluation of antagonistic characters in narrative contexts.MethodsThis systematic review analyzed findings from functional magnetic resonance imaging (fMRI) studies investigating brain activity during narrative processing, with a focus on moral and emotional evaluations of fictional antagonists. Studies were selected based on relevance, methodological rigor, and use of narrative-based stimuli. Key variables included participant demographics, types of antagonists, and narrative formats used in experimental paradigms.ResultsFindings indicate that the default mode network (DMN), particularly the medial prefrontal cortex (mPFC), is consistently activated during moral and emotional evaluations of characters. Neural synchronization in areas such as the inferior frontal gyrus (IFG) and anterior cingulate cortex (ACC) suggests that character relatability significantly influences engagement and brain activity. Variations across studies point to the influence of narrative style and participant background on neural responses.DiscussionThe evidence highlights the central role of the DMN in processing complex moral narratives and suggests that engagement with antagonistic characters involves both emotional resonance and ethical judgment. However, the generalizability of findings is limited by factors such as a lack of demographic diversity and inconsistent experimental designs. Future research should prioritize ecologically valid methodologies and diverse participant samples. This review emphasizes the need for interdisciplinary approaches combining neuroscience, psychology, and literary studies to deepen our understanding of narrative engagement.